Краткий обзор истории, этнографии и фольклора азербайджанского племени текле в Республике Грузия - Асад Алиев (Народна творчість та етнологія, 2014)
Статья посвящена тюркскому племени текле, которое проживает в регионе Гарайазы (современная Грузия). В ней исследуется история, этнография, фольклор этого племени, его устное народное творчество, кулинарное искусство; отмечается, что теклинцы обладают особенностями ремесла; особое внимание уделяется народным праздникам, свадебным и траурным обрядам. В статье также упоминается гостеприимность населения текле, его забота и уважение к старцам, отцам, матерям. The article is dedicated to the village located Garayazi region in Georgia, where Azerbaijanis live compactly. In this article it was scrutinized the history, ethnography, and folklore of Azerbaijanis living in this region. The author emphasized that they have rich folk art, ashug (folk poet) art, specific customs and traditions, and cuisine. The holidays, weddings, and funeral traditions of this region were also investigated in this article. The author stated that the people living in Tekle valley are very hospitable and honest, and elderly people, parents, are highly respected and cared for in this region.